Weight, Attractiveness, and Gender When Hiring: A Field Experiment in Spain - Catarina Goul\~ao; Juan A. Lacomba; Francisco Lagos; Dan-Olof Rooth (Institute of Labor Economics (IZA), 2023)
Being overweight or obese is associated with lower employment and earnings, possibly arising from employer discrimination. A few studies have used field experiments to show that obese job applicants are, in fact, discriminated against in the hiring process. However, whether overweight job applicants also face employer discrimination is still an open question. To this end, we have designed a correspondence testing experiment in which fictitious applications are sent to real job openings across twelve different occupations in the Spanish labor market. We compare the callback rate for applications with a facial photo of a normal weight person to the one for applications with a photo of the same person manipulated into looking overweight. Applications with a photo of the weight-manipulated male receive significantly fewer callbacks for a job interview compared to normal weight, and this differential treatment is especially pronounced in female-dominated occupations. For women, we find the opposite result. Weight-manipulated female applications receive slightly more callbacks, especially in female-dominated occupations. Our experimental design allows us to disentangle whether employers act on attractiveness or weight when hiring. For men, the weight manipulation effect is explained by an attractiveness premium, while for women we find evidence of an attractiveness penalty, as well as a weight penalty, in explaining the effect.
Keywords: J64; J71; 330; obesity; overweight; gender; attractiveness; hiring; correspondence testing